Acrylamide exposure represses neuronal differentiation, induces cell apoptosis and promotes tau hyperphosphorylation in hESC-derived 3D cerebral organoids. (October 2020) - Bu, Qian; Huang, Yan; Li, Meng; Dai, Yanping; Fang, Xin; Chen, Ke; Liu, Qian; Xue, Aiqin; Zhong, Kai; Huang, Yina; Gao, Hong; Cen, Xiaobo
Abstract: Acrylamide (ACR) is a common food contaminant with neurotoxic effects that are formed in the Maillard browning reaction during the heat processing of food. Importantly, pregnant women are also exposed to ACR in food during pregnancy and thus, the fetus is likely affected. However, the mechanisms of ACR-caused neurotoxicity on human brain development are still unclear. Many recent studies employed cerebral organoids based on human embryonic stem cells (hESC) for investigating human neurodevelopmental disorders and toxicity. Here, we generated hESC-derived cerebral organoids to evaluate the neurodevelopmental toxicity of ACR. The results indicated that exposure to ACR significantly altered the transcriptional profile, increased nuclear factor erythroid 2-related factor 2 (NRF2)-mediated gene expression, induced cell apoptosis, repressed neuronal differentiation, and promoted tau hyperphosphorylation in cerebral organoids, which may contribute to ACR-induced neurodevelopmental toxicity. These results indicate that the risk of transplacental exposure of the fetus to ACR should be evaluated and pregnant mothers should limit their exposure to ACR. Highlights: The cerebral organoids are generated to investigate the neurodevelopmental toxicity of acrylamide. Acrylamide exposure alters the transcriptional profile of cerebral organoids. Impairment of neuronal differentiation in acrylamide treated cerebral organoids. Accumulation of tau hyperphosphorylation in acrylamide treated cerebral organoids. Acrylamide induces NRF2-mediated pathway activation and cell apoptosis in cerebral organoids.